1998
DOI: 10.1152/ajpendo.1998.274.2.e224
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of thyroid hormone on renin secretion, content, and mRNA in juxtaglomerular cells

Abstract: The effects of thyroid hormone on renin secretion, renin content, and renin mRNA levels in juxtaglomerular (JG) cells harvested from rat kidneys were determined by radioimmunoassays and reverse transcriptase-polymerase chain reaction. Despite a lack of immediate effect, incubation with triiodothyronine dose dependently increased renin secretion during the first 6 h and elevated renin content and renin mRNA levels during the subsequent period. Simultaneous incubation with triiodothyronine and the calcium ionoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…JG cells had a 48-h rest period before the beginning of the experiments. Immunofluorescence staining for renin confirmed that 87 4% of the cells (n 5 primary cultures) were positive for renin at 60 h after isolation (11)(12)(13)(14).…”
Section: Primary Culture Of Rat Jg Cellsmentioning
confidence: 82%
See 2 more Smart Citations
“…JG cells had a 48-h rest period before the beginning of the experiments. Immunofluorescence staining for renin confirmed that 87 4% of the cells (n 5 primary cultures) were positive for renin at 60 h after isolation (11)(12)(13)(14).…”
Section: Primary Culture Of Rat Jg Cellsmentioning
confidence: 82%
“…In accordance with the guidelines and practices established by the Keio University Animal Care and Use Committee, JG cells were isolated from kidneys of male Sprague-Dawley rats (100-150 g) as previously described (11)(12)(13)(14). JG cells were suspended at 10 6 cells/ml in culture medium consisting of RPMI 1640 with 25 mmol/l N-2-hydroxyethylpiperazine-N -2-ethane sulfonic acid, 0.3 g/l L-glutamine, 100 µg/ml streptomycin, 100 U/ml penicillin, 0.66 U/l insulin, and 10% fetal bovine serum.…”
Section: Primary Culture Of Rat Jg Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, administration of ACE-inhibitors in hyperthyroid animals with hypertension led to a decrease in BP to normal levels with increased heart rate and CO, indicating that in hyperthyroidism the predominant factor of hypertension is the RAS system and not the increased CO (31). Data from in vitro studies reported that administration of thyroid hormones increases the synthesis and secretion of renin by the rat juxtaglomerular cells (74). Notably, there are no data regarding the synthesis or/and secretion of pro-renin and thyroid hormones.…”
Section: Thyroid the Kidney And The Renin-angiotensin Systemmentioning
confidence: 99%
“…Ichihara et al (1998) found that triiodothyronine (T 3 ) administration increases renin secretion, renin content, and renin mRNA in rat juxtaglomerular cell cultures. Various authors observed this direct action in cardiac tissue from hyperthyroid rats and reported that thyroid hormones directly stimulate renin mRNA and the promoter activity of the human renin gene via thyroid hormone regulating elementdependent mechanisms (Gilbert et al 1994, Kobori et al 1997a,b, 2001).…”
Section: Reninmentioning
confidence: 99%